Inhibitory Potential of the Drimane Sesquiterpenoids Isotadeonal and Polygodial in the NF-kB Pathway - Víctor Marín; Cecilia Villegas; Ayorinde Víctor Ogundele; Jaime R. Cabrera-Pardo; Bernd Schmidt; Cristian Paz; Viviana Burgos (Molecules)
Inflammation contributes to the onset and development of many diseases, including neurodegenerative diseases, caused by the activation of microglia, leading to neurological deterioration. Nuclear factor-κB (NF-κB) is one of the most relevant pathways for identifying anti-inflammatory molecules. In this study, polygodial and isotadeonal, two drimane sesquiterpene dialdehydes, were isolated from Drimys winteri, a medicinal tree of the Mapuche people in Chile. Isotadeonal, or epi-polygodial, was obtained from polygodial by epimerization in basic media (60% yield, Na2CO3, r/t, 24 h). Both sesquiterpenoids were evaluated on the NF-κB pathway, with the result that isotadeonal inhibited the phosphorylation of IκB-α at 10 μM with higher potency by Western blotting. The final inhibition of the pathway was evaluated using a SEAP reporter (secreted alkaline phosphatase) on THP-1 cells. Isotadeonal inhibited SEAP with higher potency than polygodial, quercetin, and CAPE (phenethyl ester of caffeic acid). In silico analysis suggests that the α-aldehyde of isotadeonal adopts a more stable conformation in the active pocket of IκB-α than polygodial.